Cuantificación espectrofotométrica de taninos en hojas de piper aduncum procedentes de la provincia de Otuzco, departamento La Libertad - Vega Ybañez, Luz Del Rosario (2014)
The purpose of this investigation was the quantification of tannins in the hydroalcoholic extract of the leaves of Piper aduncum "matico". The samples of the leaves were collected in the Province of Otuzco, Department of La Libertad, in the month of March- 2013. The extract was prepared using as solvent ethanol 50% v/v. The cuantification of tannins in the hidroalcoholic extract was made by the spectrofotometric method, in this way it was prepared a calibration curve using as standar tannic acid, obtaining the following equation y = 47.6x + 0.0024. The absorbance of the extract samples were read in a wavelength of 700 nm, obtaining as average 27,7814 % of tannins expressed as tannic acid. For statistic analisis it was made of use of average, standar desviation, variation coefficient and confident limits